Which one is the first choice for rapid ventricular rate atrial fibrillation in emergency department: Metoprolol or Diltiazem? A randomized clinical trial - Memiş, Mehmet Barış; Ak, Rohat; Cimilli Öztürk, Tuba; Onur, Özge; Ordu, Özgür (Journal of Surgery and Medicine, 2019)
Aim: Atrial fibrillation (AF) is the most common cardiac arrhythmia managed by emergency physicians. Primary goals of treatment are hemodynamic stabilization, ventricular rate control, and prevention of embolic complications. The aim of this study is to compare the drug responses of the patients who presented to the ED with AF with rapid ventricular response (AFRVR), their need for the second dosage and echocardiographic parameters. Methods: This is a prospective, single blind, randomized study. AFRVR patients were randomized and first group was given intravenous 0.25 mg/kg diltiazem as the calcium channel blocker; the second group was given intravenous 5 mg metoprolol. The vital findings and the clinical data of the patients in the 0, 2nd 5th, 15th and 30th minutes were recorded after each treatment. After the initial dosing, the patients having heart rate <110 beat/min in the 30th minutes were regarded as responders to the initial treatment. Nonresponders took second dosage of the same drug. After the rate control of all patients, a cardiologist performed the transthoracic echocardiography (TTE)’s of all participants. Results: Fifty of the patients were given diltiazem, 50 of them were given metoprolol. 45 of them (45%) had no first dose response; whereas 55 (55%) of them had. The rate of incidence for the first dose response in the patients having diltiazem was higher than the patients having metoprolol, which was statistically significant. There is statistically significant difference between rates of the valvular heart disease seen for the patients in responsive /unresponsive groups for both drugs. But diltiazem is more successful in presence of valvular disease than metoprolol. Conclusion: In this study, we found that diltiazem is more effective in the rate control of AFRVR in emergency department. This study showed that most of atrial fibrillation patients have valvular disease, and diltiazem is more effective than metoprolol in these patients. Ejection fraction, cardiac diameters are important in drug response.